Prevalence of DeQuervain’s Tenosynovitis among Clinical Physical Therapists in Islamabad: A cross-sectional study - Shamaas Irfan, Minahil Butt , Ishaq Ahmed, Husnain Khalid, Ramsha Masood , Anum Zafar, Uzair Ahmad, Muheeb ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Aims: To determine the prevalence of De Quervain’s tenosynovitis among clinical physical therapists in Islamabad. Study design: A descriptive cross-sectional study Place and duration: We conducted this study among clinical physical therapists working in hospitals and clinics of Rawalpindi and Islamabad from Feb 2022 to Aug 2022. Methods: We included 288 clinical physical therapists that were selected through non-probability quota sampling. Both male and female clinical physical therapists with ages ranging from 25 to 50 yrs having thumb pain, with one year of clinical experience who worked for 4 to 8 hours per day at least 4 days a week were included in the study. The De Quervain tenosynovitis was diagnosed in participants having tenderness at the base of the thumb and a positive Finkelstein test. A positive Finkelstein sign indicates pain over the region of the abductor pollicis and extensor pollicis tendon. The data were collected and statistically analyzed using SPSS version 26. Results were shown in the form of frequency tables and graphs. Results: Out of 288 participants, 77(26.73%) had tenderness at the base of the thumb and 77(26.74%) clinician physical therapists had positive Finkelstein test. This indicates that 26.73% had De Quervain’s Tenosynovitis. Out of them, 31.94% of cases were males and 21.51% were females. Out of these 77 therapists, 4(5.2%) therapists suffered from mild pain, 61 (79.2%) physical therapists experienced moderate pain while 12(15.6%) therapists with positive cases had severe thumb pain. Conclusions: The study concluded that there was a prevalence of De Quervain’s tenosynovitis among clinical physiotherapists experiencing thumb pain. Key words: De Quervain’s tenosynovitis, Physical Therapists, Finkelstein’s test, Thumb pain